KUALITAS MADU DARI 3 SPESIES LEBAH PENGHASIL MADU: Honey Quality from 3 Species of Honey Producing Bees - Jauhar Khabibi; Albayudi Albayudi; Dicky Julasdianta Ginting (Jurnal Silva Tropika, 2022)
ABSTRACTHoney is a food ingredient that has high nutritional value. The quality of honey varies greatly depending on the source of the honey-producing bees (Apis mellifera, Apis dorsata, and Trigona sp.). Data related to the quality of honey produced from these 3 types of bees have not been explored and are easily obtained widely. Though this data is very important to determine the use and utilization of honey appropriately. This study aims to analyze the quality of honey from 3 types of honey-producing bees. Honey samples from 3 species Apis mellifera, Apis dorsata, and Trigona sp. Chemical and physical tests were carried out 5 replicates for each sample. The test results were analyzed using descriptive statistics. The results showed a chemical test with water content test parameters. The honey acidity test parameters, reducing sugar content test, ash content test, water insoluble solids test were in accordance with (Indonesia National Standard) SNI. Meanwhile, for the water content parameter, only Apis mellifera was suitable. Meanwhile, in the sucrose test, only Trigona sp. which does not meet SNI. Keywords: honey, bee, species, quality ABSTRAKMadu adalah bahan pangan yang mempunyai khasiat tinggi yang kaya akan nutrisi. Mutu madu sangat beragam bergantung pada sumber jenis lebah penghasil madu (Apis mellifera, Apis dorsata, dan Trigona sp.). Data terkait kualitas madu yang dihasilkan dari 3 jenis lebah ini belum tergali dan mudah didapatkan secara luas. Padahal data ini sangat penting untuk menentukan penggunaan dan pemanfaatan madu secara tepat guna. Penelitian bertujuan menganalisi kualitas madu dari 3 jenis lebah penghasil madu. Sampel madu dari 3 spesies Apis mellifera, Apis dorsata, dan Trigona sp. diuji kimia dan fisik dilakukan 5 ulangan setiap sampel. Hasil pengujian dianalisis menggunakan statistik deskriptif. Hasil penelitian menunjukkan uji kimia dengan parameter uji kadar air. Parameter uji keasaman madu, uji kadar gula reduksi, uji kadar abu, uji padatan tak larut dalam air sesuai dengan stanadar nasional indoensia (SNI). Sedangkan pada parameter kadar air hanya Apis mellifera yang sesuai. Sedangkan pada uji sukrosa hanya madu Trigona sp. yang tidak memenuhi SNI. Kata kunci: madu, lebah, spesies, kualitas